FACTORS INFLUENCING ONLINE SOCIAL SUPPORT OF SOCIAL NETWORKING SITE USE AMONG ELDERLY PEOPLE - Jongchansitto, Patpiya; Pornsakulvanich, Vikanda (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
This study aimed to examine the factors that predicted two-way online social support frequency both receiving and giving in the context of social networking site use of elderly people. This study was based on the theory of uses and gratifications. Quantitative research with questionnaires was used to collect the data from 400 participants who were elderly people (aged 60 and over) and had participated in social networking websites in 3 months. Overall, the findings revealed that elderly people who had high self-esteem had high frequency of giving online emotional and information support. On the other hand, loneliness in elderly people had influence on low frequency of receiving online emotional support and giving online tangible social support. Moreover, entertainment motive had a positive effect on both receiving and giving online social support frequency in all three dimensions which are emotional support, tangible support, information support. In term of compulsive use positively predicted both receiving and giving online social support frequency among elderly people.